Central bank-driven mispricing - Loriana Pelizzon; Marti G. Subrahmanyam; Davide Tomio; Jun Uno (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2018)
We show that bond purchases undertaken in the context of quantitative easing efforts by the European Central Bank created a large mispricing between the market for German and Italian government bonds and their respective futures contracts. On top of the direct effect the buying pressure exerted on bond prices, we show three indirect channels through which the scarcity of bonds, resulting from the asset purchases, drove a wedge between the futures contracts and the underlying bonds: the deterioration of bond market liquidity, the increased bond specialness on the repurchase agreement market, and the greater uncertainty about bond availability as collateral.
Keywords: G01; G12; G14; 330; Central Bank Interventions; Liquidity; Sovereign Bonds; Futures Contracts; Arbitrage